DARI IMAN MENUJU AKSI: STRATEGI PENGUATAN CAPACITY BUILDING MELALUI PENDIDIKAN KRISTEN BERMAKNA - Viktor Deni Siregar; Haposan Simanjuntak; Sri Juniati Sihombing; Theresya Novelina br Lumban Gaol; Rosna Galingging; Jelita Marito Malau (Sekolah Tinggi Teologi Duta Panisal, 2026)
Christian education is often perceived as merely imparting doctrine and religious knowledge, thus failing to address the need for individual capacity development to face the challenges of the times. This situation creates a research gap between the ideal of transformative Christian education and practices that still focus solely on cognitive aspects. However, strengthening capacity building is crucial to producing Christian leaders who are not only faithful but also competent, possess integrity, and are able to make a real contribution to society. This article aims to analyze how meaningful Christian education can be used as a strategy to strengthen capacity building, by integrating faith as a spiritual foundation and action as its practical manifestation. This research uses a qualitative approach using literature studies on various theories of Christian education, capacity building, and practices of meaningful education. The analysis was conducted conceptually to formulate a framework that connects faith, the process of meaningful Christian education, and the outcomes in the form of increased individual and institutional capacity. The results of the study indicate that meaningful Christian education, which is holistic, contextual, and participatory, can bridge the gap between faith and action. Thus, Christian education not only transmits spiritual values ​​but also strengthens the capacity of students to prepare them for change and to exercise leadership in society.